ANALISIS PENDAYAGUNAAN ZAKAT PRODUKTIF BMT DALAM PENINGKATAN KESEJAHTERAAN MUSTAHIQ DI KABUPATEN BLORA - Suratno (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2018)
This paper is a study that aims to explain the utilization of zakat Productive BMT in Blora, Analyzing the factor supporting and inhibiting productive utilization of zakat BMT, Identifies the impact on the welfare BMT productive zakat mustahiq in Blora. From the results of research and discussion it was concluded that the collection of zakat was done by BMT compiled from employee salaries, zakat maal members of BMT, and zakat company. The distribution of zakat most consumptive except revolving goat. One of the factors supporting the productive utilization of zakat is awareness of the board and employees of BMT will zakat high enough, then the inhibitor is zakat productive goat a goa given sometimes experience pain or death. Mustahiq experiencing good economic changes from before and after receiving zakat goats for the business productive. Mustahiq needs are met both material and spiritual, the need for clothing, food, shelter and health with state security, safe, peaceful, and peace.